2002
DOI: 10.1136/jnnp.73.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Vim thalamotomy for Holmes' tremor secondary to midbrain tumour

Abstract: Holmes' (rubral or midbrain) tremor is an unusual combination of 2 Hz to 5 Hz rest, postural, and kinetic tremors of an upper extremity. This tremor has been considered to result from the lesions in the vicinity of the red nucleus in the midbrain.There has been no systematic analysis of the surgical target in the Holmes' tremor so far of nucleus ventrointermedius (Vim) or globus pallidus interna. This 26 year old man gradually developed a disabling midbrain tremor involving both the distal and proximal parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…There was also no delayed loss of efficacy, as reported by others [1] . Although VIM thalamotomy and posteroventral pallidotomy may lead to long-term benefits in HT as well [19,20] , DBS should be the preferred procedure, given its superior safety profile [21] . The best target site is still a matter of debate, although this series and most case reports favor the VIM (see table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was also no delayed loss of efficacy, as reported by others [1] . Although VIM thalamotomy and posteroventral pallidotomy may lead to long-term benefits in HT as well [19,20] , DBS should be the preferred procedure, given its superior safety profile [21] . The best target site is still a matter of debate, although this series and most case reports favor the VIM (see table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic and dorsal or posterior STN DBS has been described in multiple case reports in patients with HT secondary to pontomesencephalic lesions with variable short-term results. 4,[9][10][11]25,27,29,30,33,34,[37][38][39][40]43,49,50 Recently Kobayashi et al reported 2-year outcome with dual thalamic and subthalamic area stimulation in 4 patients with HT, with significant benefit.…”
Section: Prior Surgical Approaches To Htmentioning
confidence: 99%
“…3,27,29 Over the course of weeks to months, despite continuous thalamic stimulation, tremor is often refractory or recurs. 18,21,62,66 The effectiveness of ventrolateral thalamic DBS in HT remains uncertain due to the limited number of cases, relatively short follow-up, and diverse outcome scales used 1,13,42,50 (Table 1).…”
Section: Prior Surgical Approaches To Htmentioning
confidence: 99%
“…In selected cases DBS and thermocoagulation may offer an alternative therapeutic strategy. 1,8,15,16,21,23,27 Kim, et al, 15 reported on a 26-year-old man in whom unilateral Vim thalamotomy almost completely abolished Holmes tremor that had been caused by a midbrain tumor. Two additional case reports of patients with a midbrain cavernous angioma 16,23 document good to excellent clinical improvements in Holmes tremor following thalamic Vim stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,17,18 On the contrary, in individual cases, stereotactic thalamotomy, 15 pallidotomy, 19 and thalamic DBS 16,26 have been reported to alleviate Holmes tremor. Note that following DBS, clinical improvements can occur in associated dystonia and rigidity as well as tremor, as demonstrated in this study and not described previously.…”
mentioning
confidence: 99%